What is the value of Facebook? Evidence from the Schwartz/Moon model. Issue 3 (5th July 2019) - Schosser, Josef; Ströbele, Heiko
Abstract : Purpose: On May 17, 2012, the social networking company Facebook Inc. fixes its initial public offering (IPO) price at 38.00 a share. Over the next couple of months, contrary to expectations raised by previous IPOs, the stock price crashes more than 50 per cent. Immediately, the question arises whether the issuer's or the stock market's pricing of the share are in line with the firm's fundamentals. Thus, the purpose of this paper is to determine the company value in close proximity to the date of IPO. Design/methodology/approach: As Facebook is an archetypal internet growth company, it is evaluated using the Schwartz/Moon model. This approach features significant advantages over traditional valuation models and more adequately captures the characteristics of growth companies. Findings: As of September 30, 2012, the fundamental share value determined was 26.53, which exceeded the market price per share of 22.66 by 22.48 per cent, but was far less than the IPO stock price. The subsequent sensitivity analysis reveals the robustness of the result to key input parameters. Originality/value: The results raise doubts about the IPO price of Facebook. Furthermore, this paper is of value from a more conceptual perspective in that an extended version of the Schwartz/Moon model is provided. Beyond extensions previously discussed in the subject-based literature, the authors include stochastic interest rates (as an additional source of uncertainty) and investigate their valuation effects.